(untitled) (Revista Torreón Universitario, 2017)
UNAN-Managua has been conducting a process of ongoing analysis and reflection on its work, in order to raise, develop, evaluate and manage. In order to reach excellence levels in academic processes, it is essential, among other activities, the permanent evaluation of the curriculum, in order to be able to improve it continuously, as Brovelli (2001: 102) points out, "Understand that evaluating the curriculum and educational institutions is to start improving them ... ". Also, the process of evaluation and updating of the curriculum allows to incorporate the advances that are given in the field of science and technology and in this way, to be able to contribute to the efficient and timely solution to environmental problems.